2005
DOI: 10.1074/jbc.m413946200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nicotine on Lung S-Adenosylmethionine and Development of Pneumocystis Pneumonia

Abstract: Because S-adenosylmethionine (AdoMet) is required by Pneumocystis carinii in vitro, Pneumocystis infection depletes plasma AdoMet of rats and humans, nicotine reduces AdoMet of guinea pig lungs, and smoking correlates with reduced episodes of Pneumocystis pneumonia (PCP) in AIDS patients, we tested the effect of nicotine treatment on PCP using a rat model. Intraperitoneal infusion of 400 g of R-(؉) nicotine kg ؊1 h ؊1 intraperitoneal for 21 days caused a 15-fold reduction in lung AdoMet although neither plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 53 publications
(32 reference statements)
3
23
1
Order By: Relevance
“…A recent report by GORDIN et al [14] found, in a follow-up study, that actively smoking HIVinfected patients who had interrupted HAART had an increased risk of bacterial pneumonia. The effect of smoking on the development of PCP is consistent with data from by SHIVJI et al [15] who showed that Sadenosylmethionine, a critical cellular metabolic intermediate necessary for P. jirovecii growth, is significantly reduced by nicotine exposure. This finding clearly explains the reduced rate of PCP among smoking AIDS patients [15].…”
Section: By Dividing Patients According To Cd4supporting
confidence: 80%
“…A recent report by GORDIN et al [14] found, in a follow-up study, that actively smoking HIVinfected patients who had interrupted HAART had an increased risk of bacterial pneumonia. The effect of smoking on the development of PCP is consistent with data from by SHIVJI et al [15] who showed that Sadenosylmethionine, a critical cellular metabolic intermediate necessary for P. jirovecii growth, is significantly reduced by nicotine exposure. This finding clearly explains the reduced rate of PCP among smoking AIDS patients [15].…”
Section: By Dividing Patients According To Cd4supporting
confidence: 80%
“…22 In contrast, infusion of nicotine into the rat depletes lung AdoMet levels by increasing lung polyamine catabolic/anabolic cycling and/or excretion. 23 We noted that the highest (fourfold) levels of plasma AdoMet were in lung cancer patients who actually had significantly lower pack-years of smoking than our high-risk smokers (Figs 1 , 2) consistent with the concept that lung cancer rather than smoking elevated AdoMet. Skelly and colleagues 24 have published results of plasma AdoMet concentrations in a variety of human infectious diseases (bacterial pneumonia, tuberculosis, asymptomatic HIV, cryptococcosis), finding levels similar to our control subjects (100 to 150 nmol/L) and demonstrated a decline after treatment.…”
Section: Discussionsupporting
confidence: 70%
“…Blanchet et al 92 observed that nicotineinduced inhibition of macrophage function may actually protect against infl ammatory lung processes such as HP by decreasing the number of alveolar macrophages in the lungs of experimental animals and decreasing infl ammatory cytokine production. Further, Shivji et al 93 reported recently that chronic nicotine exposure results in a reduction of lung S-adenosylmethionine (AdoMet), which is required for growth of Pneumocystitis carinii . As such, smoking and nicotine protect against Pneumocystitis .…”
Section: Immune Systemmentioning
confidence: 99%